A hierarchical analysis of predictors of perioperative competency in Chinese operating room nurses - Cong Fu; Kulwadee Abhicharttibutra; Wanchai Lertwatthanawilat; Orn-Anong Wichaikhum (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: Perioperative competency among operating room (OR) nurses is essential for ensuring patient safety and effective surgical care. Guided by Bronfenbrenner’s bioecological model, particularly the Person component, this study examined how key individual characteristics contribute to perioperative competency among nurses working in tertiary hospitals in China. Objective: This study aimed to hierarchically examine the predictive power of key person characteristics (including demographics, specialized resources, and force characteristics) on perioperative competency. Methods: A cross-sectional survey was conducted among 287 OR nurses from five tertiary hospitals in Hebei Province, China. Data were collected between September 1 and November 30, 2024. Using a predictive correlational design, hierarchical multiple regression analysis was performed. Demographics (gender, marital status, educational level, professional job title) were entered in Block 1, followed by core predictors (years of experience, specialized training, empowerment, self-efficacy, and resilience) in Block 2, using the enter method for each block. Key constructs were measured with validated scales: perioperative competency, resilience, individual empowerment, and work self-efficacy. Results: The final regression model was significant, explaining 77.3% of the total variance in perioperative competency (Adjusted R² = 0.773, F = 88.449, p < 0.001). Special OR training (β = 0.534, p < 0.001) and years of OR experience (β = 0.395, p < 0.001) were the strongest predictors. Among force characteristics, individual empowerment (β = 0.233, p < 0.001), resilience (β = 0.199, p < 0.001), and work self-efficacy (β = 0.197, p < 0.001) all demonstrated significant positive effects. Conclusion: Both specialized resources and force characteristics significantly contribute to perioperative competency. Strategies that strengthen professional training, clinical experience, and positive psychological attributes may help enhance competency among OR nurses.